Super-ions of sodium cations with hydrated hydroxide anions: inorganic structure-directing agents in zeolite synthesis. Issue 9 (13th August 2021) - Asselman, Karel; Pellens, Nick; Radhakrishnan, Sambhu; Chandran, C. Vinod; Martens, Johan A.; Taulelle, Francis; Verstraelen, Toon; Hellström, Matti; Breynaert, Eric; Kirschhock, Christine E. A.
Abstract : NMR-crystallography, combining advanced NMR, diffraction and molecular modelling reveals a zundel based super-ion to template hydroxysodalite. Abstract : In inorganic zeolite formation, a direct correspondence between liquid state species in the synthesis and the supramolecular decoration of the pores in the as-made final zeolite has never been reported. In this paper, a direct link between the sodium speciation in the synthesis mixture and the pore structure and content of the final zeolite is demonstrated in the example of hydroxysodalite. Super-ions with 4 sodium cations bound by mono- and bihydrated hydroxide are identified as structure-directing agents for the formation of this zeolite. This documentation of inorganic solution species acting as a templating agent in zeolite formation opens new horizons for zeolite synthesis by design.